Implementation of PWM Control of DC Split Converter Fed Switched Reluctance Motor Drive - P. Srinivas (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The phase winding of Switched Reluctance Motor is excited during the positive increasing region of the phase inductance to get the motoring action. This is performed through a converter. This paper presents the speed control of DC Split converter fed 4 phase 8/6 Switched Reluctance Motor drive using PWM controller. The speed of the motor is controlled by varying the duty ratio of the PWM controller.  Simulation results are verified with hardware implementation of the controller. The Hall sensors provided in the motor provide signals corresponding to the position of the rotor. The pulses to the IGBT switches are generated by TMS320F2407A DSP controller. The waveforms of the PWM signals and Hall sensor signals are captured by means of Digital Storage Oscilloscope. Motor phase currents, phase voltages and associated numerical values are captured and analyzed by Power Analyzer. Steady state analysis of the drive has been carried out.